Antibacterial Activity Test of Tropical Plants (Morinda citrifolia) and (Melaleuca leucadendra) against Pneumonia-causing Bacteria - Nadila Pitriani; Hermansyah Hermansyah; Ferlinahayati Ferlinahayati (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
This study aims to determine the antibacterial activity of tropical plants against bacteria that cause pneumonia. The initial stage is to prepare samples of tropical plants that are macerated with methanol and produce a thick extract, namely 38.3881 grams of noni fruit with a yield of 13.422%, and cajuput leaves as much as 11.211 grams with a yield of 3.38%. The next step, each sample was fractionated using VLC then produced ethyl acetate fraction and methanol fraction. Bacterial activity test was carried out by disc diffusion method, and the MIC value was determined by liquid dilution method using UV-Vis spectrophotometry. Based on the results of antibacterial testing, the noni fruit extract and cajuput extract obtained the most active fraction in response to inhibiting bacteria causing pneumonia (S. pneumonia, S. aureus and K. pneumoniae) was the ethyl acetate fraction with a strong average response zone of inhibition up to very strong with MIC value of ethyl acetate fraction from noni fruit extract 6250 ppm each and MIC value of ethyl acetate fraction from cajuput extract (Melaleuca leucadendra) 390.625 ppm each; 390.625 ppm; and 195.3125 ppm.